Differential expression of junctional adhesion molecules in different stages of systemic sclerosis. Issue 1 (27th December 2012) - Manetti, Mirko; Guiducci, Serena; Romano, Eloisa; Rosa, Irene; Ceccarelli, Claudia; Mello, Tommaso; Milia, Anna Franca; Conforti, Maria Letizia; Ibba‐Manneschi, Lidia; Matucci‐Cerinic, Marco
Abstract Objective Systemic sclerosis (SSc) is characterized by early perivascular inflammation, microvascular endothelial cell (MVEC) activation/damage, and defective angiogenesis. Junctional adhesion molecules (JAMs) regulate leukocyte recruitment to sites of inflammation and ischemia‐reperfusion injury, vascular permeability, and angiogenesis. This study was undertaken to investigate the possible role of JAMs in SSc pathogenesis. Methods JAM‐A and JAM‐C expression levels in skin biopsy samples from 25 SSc patients and 15 healthy subjects were investigated by immunohistochemistry and Western blotting. Subcellular localization of JAMs in cultured healthy dermal MVECs and SSc MVECs was assessed by confocal microscopy. Serum levels of soluble JAM‐A (sJAM‐A) and sJAM‐C in 64 SSc patients and 32 healthy subjects were examined by enzyme‐linked immunosorbent assay. Results In control skin, constitutive JAM‐A expression was observed in MVECs and fibroblasts. In early‐stage SSc skin, JAM‐A expression was strongly increased in MVECs, fibroblasts, and perivascular inflammatory cells. In late‐stage SSc, JAM‐A expression was decreased compared with controls. JAM‐C was weakly expressed in control and late‐stage SSc skin, while it was strongly expressed in MVECs, fibroblasts, and inflammatory cells in early‐stage SSc. Surface expression of JAM‐A was higher in early‐stage SSc MVECs and increased in healthy MVECs stimulated with early‐stage SSc sera. JAM‐C was cytoplasmic in resting healthy MVECs, while it was recruited to the cell surface upon challenge with early‐stage SSc sera. Early‐stage SSc MVECs exhibited constitutive surface JAM‐C expression. In SSc, increased levels of sJAM‐A and sJAM‐C correlated with early disease and measures of vascular damage. Conclusion Our findings indicate that JAMs may participate in MVEC activation, inflammatory processes, and impaired angiogenesis in different stages of SSc.